2004
DOI: 10.1210/en.2003-0319
|View full text |Cite
|
Sign up to set email alerts
|

Osteoprotegerin Expression and Secretion Are Regulated by Calcium Influx through the L-Type Voltage-Sensitive Calcium Channel

Abstract: Our previous studies showed that 1,25-dihydroxyvitamin D3 [1,25(OH)2D3] modulates the activity of the Ca(V1.2) alpha-subunit of the L-type voltage-sensitive calcium channel (VSCC) by two temporally distinct mechanisms. First, 1,25(OH)2D3 rapidly modulates local Ca2+ permeability in the plasma membrane of the proliferating osteoblast. Second, treatment with 1,25(OH)2D3 reduces biosynthesis of Ca(V1.2) such that transcript levels are half of original levels after 24 h. Osteoprotegerin (OPG) and receptor activato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
36
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 48 publications
8
36
0
Order By: Relevance
“…Thus, these data extend previous findings for a Ca V 1.2 role in mandibular development (4) Because these mouse models all employed Cre recombinases that drove Ca V 1.2 TS expression in osteoblast lineages, and not in osteoclasts or their precursors, we conclude that the observed anticatabolic responses resulted from an increase in the Rankl/Opg expression ratio and OPG secretion and consequent extrinsic inhibition of osteoclastogenesis. This is consistent with previous data showing that Ca V 1.2 regulates OPG secretion (27) and the well-defined roles for Ca V 1.2 channels in promoting hormone secretion from endocrine tissue. Moreover, our lacZ expression data showed that Ca V 1.2 is expressed within bone tissue where osteoblast precursor cells reside, and previous RNA-seq data showed no expression of Ca V 1.2 in murine BMMs or during osteoclast differentiation (15) TS suggests a possible therapeutic strategy for osteoporotic or osteopenic conditions.…”
Section: Discussionsupporting
confidence: 93%
“…Thus, these data extend previous findings for a Ca V 1.2 role in mandibular development (4) Because these mouse models all employed Cre recombinases that drove Ca V 1.2 TS expression in osteoblast lineages, and not in osteoclasts or their precursors, we conclude that the observed anticatabolic responses resulted from an increase in the Rankl/Opg expression ratio and OPG secretion and consequent extrinsic inhibition of osteoclastogenesis. This is consistent with previous data showing that Ca V 1.2 regulates OPG secretion (27) and the well-defined roles for Ca V 1.2 channels in promoting hormone secretion from endocrine tissue. Moreover, our lacZ expression data showed that Ca V 1.2 is expressed within bone tissue where osteoblast precursor cells reside, and previous RNA-seq data showed no expression of Ca V 1.2 in murine BMMs or during osteoclast differentiation (15) TS suggests a possible therapeutic strategy for osteoporotic or osteopenic conditions.…”
Section: Discussionsupporting
confidence: 93%
“…Bergh et al (4) have described a model in which the calcium signals generated by the regulatory activity of L-type voltage-sensitive channels can regulate OPG expression and secretion by means of calmodulin-sensitive protein kinase signaling; blocking the activity of these channels reduces the level of OPG expression and secretion in primary calvarial organ (4).…”
Section: Discussionmentioning
confidence: 99%
“…Ca 2+ helps regulate a variety of cellular functions in many different cells, including germ cells and somatic cells in the testis, as well as spermatozoa, in response to endocrine hormones and local regulators [7][8][9][10][11]. Moreover, alteration of the Ca 2+ signalling pathway has a drastic impact on many cellular physiologies [12][13][14][15] [5,6,17], while other studies have argued that voltage-dependent Ca 2+ channels (VDCCs) are also involved [18][19][20]. Recently, mibefradil, a new nondihydropyridine calcium antagonist, has been shown to block the T-type Ca 2+ channel with a high affinity and selectivity in a variety of cell preparations [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%